FORMATION OF COMPETENCIES IN THE STUDY OF THE RUSSIANLANGUAGE (Scientific journal of the Fergana State University, 2025)
The article considers measures to increase the professional competence of specialists in the system of teaching the Russian language and literature. The competency approach is one of the leading schools of modern linguistics. The description of the Russian language provides material for students to get acquainted with the main abilities formed in the process of learning the Russian language, the content, technologies and forms of a literate approach to the process of learning the Russian language. Currently, the problem of developing professional competence of specialists in the theory and practice of language teaching is one of the main common problems of professional development. The communicative direction of teaching the Russian language implies the practical purpose of teaching – the development of speech communication skills. Teaching communication in the process of communication is the main feature of communication. Communicative abilities dictate knowledge and skills in the main types of speech activity based on speech information: speaking; listening; reading; writing, which makes it possible to understand the cultural-emotional potential of the language as a means of expressing national culture, international cultural code, the interaction of language and people's history, the interaction of language and thinking, ethnomadanic features of the language.